ENERGY RESOURCES OF GREECE: FACTS AND MYTHS - Christanis, K. (Bulletin of the Geological Society of Greece, 2010)
Energy is essential for human life and civilization being extremely crucial for the continuation of human development. The main concern worldwide is to meet rising demand for energy in a sustainable way and at reasonable cost. Greece has significant lignite and some uranium reserves and remarkable potentials in renewable sources. However, the primary energy mix used in the country today is based on lignite and imported oil and gas, the latter increasing country’s dependency on foreign suppliers, while renewable sources play a minor role. The public opinion is misinformed and sometimes confused in respect of some aspects concerning energy issues. This strongly influences important decisions on energy projects and in overall, the energy policy of the country.